Pelatihan Pemanfaatan Cloud Storage dan Weblog bagi SMA 11 Pulau Buluh - Cosmas Eko Suharyanto; Alfannisa Annurrallah Fajrin (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2020)
ABSTRACTTechnology has changed the way people communicate, interact and act in various tasks and activities. One of them is how people store digital data in a storage medium. Conventional storage media such as hard disks, flash disks, CD / DVDs have begun to be abandoned. One reason has begun to be abandoned is that important data is often lost along with the loss of the media. Technology, especially the internet, has become one of the solutions in the world of storage media, namely the presence of cloud technology through cloud storage. In addition to being the answer, the internet is also a means of communication through weblog media or often abbreviated as blogs. Almost the same as Cloud Computing technology, Weblog is a blog collaboration tool so that not only a user can do blogging activities, but is done together, from anywhere and at any time. Weblogs can be an effective media of information about an organization's activities. These two things are the background of the plan of Community Service activities at SMAN 11 Buluh Island Batam. For teachers, cloud storage technology has been introduced through lectures and hands-on training, while for the student council management has been trained on how to design a weblog in accordance with the needs of the school, especially the students. Teachers can take advantage of the benefits of cloud storage for various purposes. The management of OSIS SMAN 11 Buluh Islah Batam can have a means of communication and creativity event with webloging activities.Â ABSTRAKTeknologi telah merubah cara orang berkomunikasi, berinteraksi dan beraksi dalam berbagai tugas dan aktivitasnya. Salah satunya bagaimana orang menyimpan data-data digital dalam sebuah media penyimpanan. Media penyimpanan konvensional seperti hard disk, flash disk, CD/DVD telah mulai ditinggalkan. Salah satu alasan sudah mulai ditinggalkan yaitu data penting sering hilang bersamaan dengan hilangnya media tersebut. Teknologi khususnya internet telah menjadi salah satu solusi dalam dunia media storage yaitu hadirnya teknologi cloud melalui cloud storage. Selain menjadi jawaban tersebut, internet juga menjadi sarana komunikasi melalui media weblog atau sering disingkat dengan blog. Hampir sama seperti teknologi Cloud Computing, Weblog adalah sarana kolaborasi blog agar tidak hanya seorang user saja yang dapat melakukan aktivitas blogging, namun dikerjakan secara bersama-sama, dari mana saja dan kapan saja. Weblog dapat menjadi media informasi yang efektif tentang suatu kegiatan organisasi. Kedua hal tersebut yang melatar belakangi rencana kegiatan Pengabdian kepada Masyarakat di SMAN 11 Pulau Buluh Batam. Bagi para guru telah diperkenalkan teknologi cloud storage melalui ceramah dan pelatihan langsung, sedangkan bagi pengurus OSIS telah dilatih bagaimana mendesain sebuah weblog sesuai dengan kebutuhan sekolah khususnya para siswa-siswinya. Para guru dapat memanfaatkan berbagai keunggulan pengimpanan awan untuk berbagai keperluan. Pengurus OSIS SMAN 11 Pulau Buluh Batam dapat memiliki sarana komunikasi dan ajang kreatifitas dengan aktivitas webloging.